2017
DOI: 10.3389/fpls.2017.02037
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glutathione Mediates Pheno-Ultrastructure, Kinome and Transportome in Chromium-Induced Brassica napus L.

Abstract: Chromium (Cr) as a toxic metal is widely used for commercial purposes and its residues have become a potential environmental threat to both human and plant health. Oilseed rape (Brassica napus L.) is one of the candidate plants that can absorb the considerable quantity of toxic metals from the soil. Here, we used two cultivars of B. napus cvs. ZS 758 (metal-tolerant) and Zheda 622 (metal-susceptible) to investigate the phenological attributes, cell ultrastructure, protein kinases (PKs) and molecular transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 79 publications
(96 reference statements)
2
32
0
Order By: Relevance
“…It has been also reported that mitochondria were underdeveloped in the Brassica napus seedlings that were exposed to 400 µM Cr as compared seedlings exposed to control conditions [41,120]. The ultrastructural investigations also revealed that Cr(VI) stress alters plastid structure, more specifically, chloroplast, with a spherical and contracted morphology [120][121][122][123]. The irregular shape and size of the chloroplast with contained large plastoglobuli and starch grains were reported in Spirodela poyrhiza seedlings that were exposed to high Cr(VI)-level [23].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 94%
See 2 more Smart Citations
“…It has been also reported that mitochondria were underdeveloped in the Brassica napus seedlings that were exposed to 400 µM Cr as compared seedlings exposed to control conditions [41,120]. The ultrastructural investigations also revealed that Cr(VI) stress alters plastid structure, more specifically, chloroplast, with a spherical and contracted morphology [120][121][122][123]. The irregular shape and size of the chloroplast with contained large plastoglobuli and starch grains were reported in Spirodela poyrhiza seedlings that were exposed to high Cr(VI)-level [23].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 94%
“…Exposure to high Cr-concentration causes mitochondrial damages, such as outer membrane rupture, swelling, deformed or altered internal cristae, dense electron accumulated materials, and spherical morphology [23,118,119]. It has been also reported that mitochondria were underdeveloped in the Brassica napus seedlings that were exposed to 400 µM Cr as compared seedlings exposed to control conditions [41,120]. The ultrastructural investigations also revealed that Cr(VI) stress alters plastid structure, more specifically, chloroplast, with a spherical and contracted morphology [120][121][122][123].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have indicated that chlorophyll b contents is more disturbed then chlorophyll a 39 . Rafaqat et al, reported the decline in photosynthetic rate in Brassica napus L. due to the elevated stress of chromium 5 . All the Pb treatments significantly (p ≤ 0.01; 0.05) decrease the mineral contents and the quality attributes of the wheat (Table 4).…”
mentioning
confidence: 99%
“…Gill et al ., reported increased size and number of starch grains due to chromium in oilseed rape cultivars 24 . The presence of heavy metals revealed elite molecular transporters (MTs) genes that were responsible for water transmembrane transporter activity 5 . The results of the Pb accumulation in wheat plant including root, shoot and seed were depicted in the (Table 6).…”
mentioning
confidence: 99%